2022
DOI: 10.1111/opo.13022
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis on the agreement of non‐cycloplegic and cycloplegic refraction in children

Abstract: Objective: To determine the diagnostic agreement of non-cycloplegic and cycloplegic refraction in children. Method:The study methodology followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Electronic databases were searched for comparative studies exploring refraction performed on children under noncycloplegic and cycloplegic conditions. There was no restriction on the year of publication; however, only publications in the English language were eligible. Inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 59 publications
2
14
0
2
Order By: Relevance
“…The results of the current study indicate that for the spherical equivalent, there is a risk of myopic overcorrection without the use of cyclopentolate. This is well known for a variety of measurement techniques that do not require the direct cooperation of the subject, such as autorefraction,18 19 28–34 retinoscopy28 35 and photorefraction 36 37. A similar trend can be observed for wavefront-assisted objective refraction.…”
Section: Discussionsupporting
confidence: 56%
“…The results of the current study indicate that for the spherical equivalent, there is a risk of myopic overcorrection without the use of cyclopentolate. This is well known for a variety of measurement techniques that do not require the direct cooperation of the subject, such as autorefraction,18 19 28–34 retinoscopy28 35 and photorefraction 36 37. A similar trend can be observed for wavefront-assisted objective refraction.…”
Section: Discussionsupporting
confidence: 56%
“…Meta-analysis and study on children aged 4 to 15 showed that, non-cycloplegia refraction resulted in a mean SE difference of −0.60D compared to cycloplegia, with greater differences observed in younger participants and in eyes with hyperopic refraction degree [47,48]. Therefore, the influence of noncycloplegia data on this study could be limited.…”
Section: Discussionmentioning
confidence: 89%
“…Cycloplegic refraction is well recommended in young children [17], whereas there is no consensus on whether the ocular components be measured before or after cycloplegia. In clinical practice, ocular biometry could be performed during the intervals of applying cycloplegic drops to save time.…”
Section: Discussionmentioning
confidence: 99%